2018
DOI: 10.1101/384982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Condensin controls mitotic chromosome stiffness and stability without forming a structurally contiguous scaffold

Abstract: During cell division, chromosomes must be folded into their compact mitotic form to ensure their segregation. This process is thought to be largely controlled by the action of condensin SMC protein complexes on chromatin fibers. However, how condensins organize metaphase chromosomes is not understood. We have combined micromanipulation of single human mitotic chromosomes, sub-nanonewton force measurement, siRNA interference of condensin subunit expression, and fluorescence microscopy, to analyze the role of co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In the past, mitotic chromosome stiffness has been measured and it was found that mitotic chromosomes had a chromatin network structure [9]. Several factors, including condensin, have been found to affect chromosome stiffness [46]. We aimed to identify whether cell stages and aging could influence chromosome stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, mitotic chromosome stiffness has been measured and it was found that mitotic chromosomes had a chromatin network structure [9]. Several factors, including condensin, have been found to affect chromosome stiffness [46]. We aimed to identify whether cell stages and aging could influence chromosome stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomes stiffness has been extensively studied in various mitotic cells, revealing similarities and differences in chromosomes stiffness among different cell types [27][28][29].…”
Section: Chromosome Stiffness From MI Oocytes Is About 10 Times Highe...mentioning
confidence: 99%
“…This chromosome axis, which also contains topoisomerase II, was originally proposed to form a rigid proteinaceous scaffold from which DNA loops are suspended [ 17 , 18 , 19 ]. Consistent with this “scaffolding” model, condensins impart structure and stiffness to mitotic chromosomes, allowing resistance to pulling forces exerted by the spindle in cells [ 20 , 21 , 22 , 23 , 24∗ , 25 ] or to micromanipulations on purified chromosomes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the mitotic bottlebrush structure formed by consecutive loops extruded by condensins, interphase loops formed by cohesin are short-lived, regulated by boundaries imposed by the protein CTCF, and interspersed with gaps [ 90 , 94∗ , 95∗ , 96 , 97 ]. This altered cross-link distribution leads to a less constrained chromatin state than that observed in mitosis, which may explain why interphase chromatin is more mobile than mitotic chromatin [ 26 , 27 , 98∗ , 99 , 100 , 101∗ ] ( Figure 4 ). The functional consequences of increased interphase chromatin mobility, and the interplay between interphase loop extrusion and the regulation of genome expression and maintenance, are now beginning to be understood.…”
Section: Introductionmentioning
confidence: 99%